Correlations Between Urban Green Areas and Euglossine Males’ Abundance - Alves, Sônia Guimarães; Silva, Lazaro Carneiro da; Frantine-Silva, Wilson; Gaglianone , Maria Cristina (Sociobiology, 2024)
Green areas are important environments in the urban landscape where many bee species can find essential resources, such as nectar, pollen, and nesting sites. However, few studies have evaluated the effects of urban green areas attributes on bee assemblages, mainly in the bees showing high forest dependence as Euglossini bees. These orchid bees are important pollinators in the Neotropical urban ecosystems, and the forest loss associated with urbanization can negatively affect euglossine communities. Here, we evaluated the role of urban green areas (UGAs) on euglossine assemblages and the abundance of dominant euglossine species. For this, we quantified different local and landscape attributes in twelve UGAs in Campos dos Goytacazes city, southeast Brazil. We expected a higher euglossine abundance in UGAs with a higher number of trees, diameter at breast height- DBH, and flower cover (%), and with a lower paved area (%), number of high buildings, and surrounding paving area (%). The euglossine males were sampled with three bait traps in each UGA. We sampled 2465 euglossine bees of four species. Eulaema nigrita Lepeletier, 1841 was the most abundant species (N = 1319; 53.5%), followed by Euglossa cordata (Linnaeus, 1758) (N = 1139; 46.2%). We found a positive effect of flower cover (%) on the abundance of these dominant euglossine species, highlighting the importance of floral resources in urban matrices, even for synanthropic species.